The sensitivity of South African plants to acute dosages of sulpher dioxide - Ashton, Elizabeth-Rose (Department of Environmental and Geographical Science, 2015)
Relative susceptibility to SO₂ has been determined for a range of South African plants. Young trees, shrubs and herbaceous species were used for experiments in which the phytotoxic effects of SO₂ were studied at different concentrations and exposure times. The plants were fumigated in an exposure chamber at ambient conditions of temperature, light intensity and relative humidity. Considerable variations in sensitivity were noted for the 63 species investigated, and, among the families well represented in the South African flora, Ericaceae were resistant while Proteaceae were sensitive to SO₂. The injury symptoms developed have been described and foliar necrosis evaluated in terms of an injury index. The results of this study form the first documented account of the susceptibility of South African plants to SO₂, and include a pictorial record of acute injury symptoms. A literature survey of current knowledge concerning visible and subtle phytotoxic effects of SO₂ is also presented.